Polymer coatings to passivate calcite from acid attack: polyacrylic acid and polyacrylonitrile. - Thompson, M; Wilkins, S; Compton, R; Viles, H (2003)
The extent of passivation of calcite toward dissolution by aqueous acids arising from polymeric coatings based on polyacrylic acid or polyacrylonitrile is evaluated using a channel flow cell technique with microdisc electrode detection. In situ passivation with polyacrylic acid leads to a reduction in the reactivity of calcite toward acid attack with a reduction in the rate constant by up to an order of magnitude compared with untreated calcite. Ex situ passivation with polyacrylic acid for 24 h results in good coverage of the calcite by the polymer but it is shown to erode from the surface when exposed to an aqueous acid solution. In contrast, polyacrylonitrile is demonstrated to form a regular coating after exposure for just 1 h and offers robust potent protection from aqueous acid attack.